Intrinsic origin of interfacial second-order magnetic anisotropy in ferromagnet/normal metal heterostructures - Gweon, Hyung Keun; Park, Hyeon-Jong; Kim, Kyoung-Whan; Lee, Kyung-Jin; Lim, Sang Ho (NATURE PUBLISHING GROUP, 2020)
Interfacial perpendicular magnetic anisotropy, which is characterized by first-order (K-1) and second-order (K-2) anisotropy, is the core phenomenon for nonvolatile magnetic devices. A sizable K-2 satisfying a specific condition stabilizes the easy-cone state, where equilibrium magnetization forms at an angle from the film normal. The easy-cone state offers intriguing possibilities for advanced spintronic devices and unique spin textures, such as spin superfluids and easy-cone domain walls. Experimental realization of the easy-cone state requires understanding the origin of K-2, thereby enhancing K-2. However, the previously proposed origins of K-2 cannot fully account for the experimental results. Here, we experimentally show that K-2 scales almost linearly with the work function difference between the Co and X layers in Pt/Co/X heterostructures (X = Pd, Cu, Pt, Mo, Ru, W, and Ta), suggesting the central role of the inversion asymmetry in K-2. Our result provides a guideline for enhancing K-2 and realizing magnetic applications based on the easy-cone state. Spintronics: Putting a twist on information flow The performance of multilayered thin films that use magnetic spins to transmit data faster than traditional electronics can be improved using new design guidelines. Materials that direct magnetic spins to point straight up from a surface so they can be electrically manipulated have gained attention for high-density memory storage. Sang Ho Lim and Kyung-Jin Lee from Korea University in Seoul and co-workers now report a technique for fabricating upward-pointing magnetic spins that also gyrate in cone-like movements. Gyrating spins can lower the energy needed for memory operations, but the materials needed to generate such magnetic states have been difficult to identify. The authors coated platinum-cobalt layers with different metal or oxide films and found that the strength of the gyrating spin state could be predicted based on textbook values of electric fields found within the thin-film layers.
Keywords: PERPENDICULAR-ANISOTROPY; FILMS